Determinants Activity of Daily Living (ADL) Elderly Tresna Werdha Nursing Home (PSTW) Special Region of Yogyakarta - Herman, Rustika; Akhriani, Herlina Nindi (Journal of Ultimate Public Health, 2018)
Background:Physiological changes affect the independence of the elderly in the activities of daily life. The purpose of this research is to know the determinants of independence of elderly in the activity of daily life.Methods: The study was designed using cross-sectional analytic study. The study population was elderly above 60 years old who lived in Tresna Werdha Nursing Home (PSTW) in Yogyakarta with a sample size of 147 elderly. Data collection using the Mini-Mental State Examination (MMSE) questionnaire and observation sheet. Multivariate analysis with multiple logistic regression.Results: The independence of the Basic Activity Daily Living (BadL) is measured by the Katz Index and the Instrumental Activity Daily Living (IADL) with the Lawton-Brody scale. The results are 22.4% of elderly dependence on BadL and 25.2% of elderly dependence on IADL. Elderly who did not perform physical activity 10.48 times the risk of experiencing dependence in BadL Compared to elderly who do physical activity (p-value = 0.000; OR = 10:48; 95% CI: 2.83-38.81). Elderly with a history of chronic disease is at risk of 8:25 times dependent on IADL Compared with the elderly without a history of chronic disease (p = 0.046; OR = 8.25; 95% CI: 1.04-65.57).Conclusion: The conclusion is Physical activity, age, and nutritional status in BadL dependence Affect while the history of chronic diseases, physical activity, and age Affects dependence in IADL. Promotional and Preventive Efforts such as routine physical activity, balanced nutrition fulfillment, clean and healthy lifestyle to Anticipate the aging process and physiological function changes.